Identification of determinants of neonatal mortality a comparison of two approaches - Aguelo-Salarda, Angelita C.
Two statistical methods of identification of determinants of neonatal mortality were demonstrated in this study: stratified analysis and logistic regression. Stratified analysis was used to determine the effect of a specific exposure factor controlling for the other variables 1 at a time. Logistic regression analysis was used to control for the joint confounding effects of the other variables in the model. Among the selected risk factors of interest in this study, the effects of birth weight and obstetrical complications were declared statistically significant. Validity and precision problems may influence the results. Therefore, the results obtained from this study should not be used to rule out the possible role of the other variables in increasing the likelihood of survival during the neonatal period.
Thesis (MS Public Health, Biometry)--University of the Philippines Manila, 1987
Keywords: Infants (Newborn) -- Mortality; Stratified analysis; Logistic regression; Neonatal mortality